Genetic deletion of the Histone Deacetylase 6 exacerbates selected behavioral deficits in the R6/1 mouse model for Huntington's disease. Issue 9 (24th June 2015) - Ragot, Alienor; Pietropaolo, Susanna; Vincent, Jean; Delage, Pauline; Zhang, Hongyu; Allinquant, Bernadette; Leinekugel, Xavier; Fischer, André; Cho, Yoon H.
Abstract: Introduction: The inhibition of the Histone Deacetylase 6 (HDAC6) increases tubulin acetylation, thus stimulating intracellular vesicle trafficking and brain‐derived neurotrophic factor (BDNF) release, that is, cellular processes markedly reduced in Huntington's disease (HD). Methods: We therefore tested that reducing HDAC6 levels by genetic manipulation would attenuate early cognitive and behavioral deficits in R6/1 mice, a mouse model which develops progressive HD‐related phenotypes. Results: In contrast to our initial hypothesis, the genetic deletion of HDAC6 did not reduce the weight loss or the deficits in cognitive abilities and nest‐building behavior shown by R6/1 mice, and even worsened their social impairments, hypolocomotion in the Y‐maze, and reduced ultrasonic vocalizations. Conclusions: These results weaken the validity of HDAC6 reduction as a possible therapeutic strategy for HD. The data are discussed in terms of additional cellular consequences and anatomical specificity of HDAC6 that could explain these unexpected effects. Abstract : We tested that reducing the Histone Deacetylase 6 (HDAC6) levels would attenuate early behavioral deficits in R6/1 Huntington's disease transgenic mice. We found that the genetic deletion of HDAC6 did not reduce the weight loss or the deficits in cognitive abilities and nest‐building behavior shown by R6/1 mice, and even worsened their social impairments and reduced ultrasonic vocalizations during social interaction.